Introduction of some Odonata species (Insecta) from northern Iran - Elham Elham Yoosefi Lafooraki; Fatemeh Rasekhi; Masoumeh Shayanmehr (تاکسونومی و بیوسیستماتیک, 2014)
Odonata are an order belonging to Paleoptera which are divided into three suborders, Anisoptera, Anisozygoptera and Zygoptera. In order to investigate Odonata fauna from Mazandaran province, adult insects were collected from several different natural habitats and were identified. The specimens were included 13 species from 10 genera belonging to seven families. Seven species belonged to Anisoptera and six species belonged to Zygoptera. The species that were marked by asterisk were recorded for the first time for Mazandaran fauna. The collected and identified species are listed as below: *Anax parthenope, *Calopteryx splendens intermedia, Calopteryx splendens orientalis, *Coenagrion vanbrinckae, Crocothemis erythraea, *Epallage fatime, *Ischnura pumilio, *Lestes virevs, *Libellula depressa, *Orthetrum albistylum, Orthetrum sabina, *Platycnemis dealbata, Sympetrum fonscolombei and Sympetrum striolatum.